Structural studies of a W-Formate dehydrogenase by X-ray crystallography – a bacterial enzyme that catalyze greenhouse gas (CO2) fixation - Klymanska, Kateryna (2022)
Mo/W-Formate dehydrogenases (Fdhs) are unique bacterial enzymes that catalyze the reversible reduction of CO2 to formate. This capability is not just a possible route for greenhouse gas sequestration, but also a possibility to create a compound that is currently used as a fuel. Only five different Fdhs have their structure solved and the two recent structures of FdhAB from Desulfovibrio vulgaris (oxidized and formate-reduced forms) showed conformational changes that may bring new insights about the catalytic mechanism. So, the main goals of this work are to attain new structures of reduced forms of FdhAB wild type and the new variant FdhAB-C872A by X-ray crystallography. Furthermore, we optimized the crystallization conditions to produce FdhAB microcrystals that will be used in serial crystallography and time resolved experiments. We crystallized FdhAB reduced with sodium dithionite and compared with the previously published formate-reduced form (PDB CODE: 6SDV). The structure of dithionite-reduced form of FdhAB was obtained by soaking the crystal with sodium dithionite and the crystals diffracted beyond 1.53 Å (the Fdh model at higher resolution). The active sites of the new dithionite-reduced structure and formate-reduced structure were then compared, and it was concluded that there are no significant differences between these two reduced states. To study the role of the conserved disulphide bridge (C845-C872, D. vulgaris numbering) in some Fdhs from Desulfovibrio, different FdhAB variants were produced by our collaborators, and we were able to crystallize and obtain different structures of the new variant FdhAB-C872A in aerobic and anaerobic conditions. The first structure of Fdh-C872A variant was obtained in aerobic conditions at a resolution of 2.27 Å. In anaerobic conditions, we obtained two good crystals of Fdh-C872A cocrystallized with sodium azide and sodium dithionite that diffracted beyond 2.4 Å 2.8 Å, respectively. The three structures of the Fdh-C872A variant are very similar, however, the active site seems to lose the sulphide ligand when the enzyme is exposed to oxygen. Comparing the active site of Fdh-C872A variant with the previous structures (PDB CODES: 6SDV and 6SDR) we concluded that it presents several differences that are the result of significant rearrangements in part of the polypeptide chain of the catalytic subunit, promoted by the disulphide bridge break. Finally, we optimized the conditions to produce micro-crystals for serial crystallography and tine resolved experiments. Several conditions were tested for FdhAB crystallization by using the crystallization robot that allowed us to plot the phases diagrams. The steps of optimization and scale-up were also successful, considering that the micro-crystals appeared, and the crystals features were reproducible. But when we tried to evaluate the crystal diffraction power in an synchrotron source, the preliminary diffraction results showed a maximum observed resolution of about 2.9 Å with very few hits. So, it was concluded that further optimization of crystallization conditions is required.